Effects of particle diameter and plate thickness on transpiration cooling for double-layer porous plates - Zhang, Xiaokai; Yan, Guanghan; Yu, Xiao; Li, Honglian; Zhang, Yi; Song, Yongchen (Frontiers in Energy Research, 2022)
Transpiration cooling is a highly efficient active thermal protection technology, which has a great application prospect in the thermal protection of hypersonic vehicles. Nevertheless, the problem of large injection pressure caused by porous structure in transpiration cooling system has been ignored in previous studies. In this work, the transpiration cooling performance of double-layer sintered metal particle plates with different particle diameter combinations and plate thickness were simulated. The results showed that the cooling effectiveness of double-layer plates was improved when the particle diameter of the porous plate in direct contact with the main stream decreased. The inner plate particle diameter and plate thickness had little effect on cooling performance. By increasing inner plate particle diameter, the coolant injection pressure can be lowered by 41% while the structural thickness was maintained. Further reducing the thickness of the outer plate to 1/4 of the total thickness can reduce the injection pressure to 38% of the single plate, which provided an optimization direction for reducing engine power consumption caused by heat dissipation.